Coordination of Complementary Sets for Low Doppler-Induced Sidelobes - Jiahua Zhu; Chongyi Fan; Yongping Song; Xiaotao Huang; Bingbing Zhang; Yanxin Ma (Remote Sensing, 2022)
Golay complementary waveforms are, by definition, able to generate narrow pulses with low sidelobes via coherent signal processing. However, while an ideal impulse can be obtained for target returns at zero-Doppler, significant sidelobes are observed at nonzero Doppler shifts. In this paper, a Generalized Binominal Design (GBD) procedure is proposed for the waveforms consisting of complementary sets in an attempt to reduce the Doppler-induced sidelobes. Our theoretical analysis as well as simulation results show that the proposed approach performs as good as existing Binominal Design method used for sidelobe suppression with Golay complementary waveforms and can also achieve around <semantics>28%</semantics> enhancement on the Doppler resolution, with an acceptable loss in peak to peak-sidelobe ratio (PPSR).